2016
DOI: 10.4012/dmj.2015-242
|View full text |Cite
|
Sign up to set email alerts
|

Bone healing capabilities of recombinant human bone morphogenetic protein-9 (rhBMP-9) with a chitosan or collagen carrier in rat calvarial defects

Abstract: The aim of this study was to examine the effects of recombinant human BMP-9 (rhBMP-9) with chitosan sponge (ChiS) or absorbable collagen sponge (ACS) on bone formation in rat calvarial defects. The defects were treated by one of the following implantations: ChiS, rhBMP-9/ChiS, ACS, rhBMP-9/ACS and no implantation. The animals were euthanized at 8 weeks for histological evaluation. The percentage of defect closure (DC) in the rhBMP-9/ACS group was significantly greater than that in the ACS group. The rhBMP-9/ A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…ACS has been shown to maintain its structure within calvarial bone defects, without collapsing, possibly because of a slow biodegradation of the cross‐linked collagen . Moreover, ACS can help to prevent diffusion of embedded cells when transplanted into bone defects .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…ACS has been shown to maintain its structure within calvarial bone defects, without collapsing, possibly because of a slow biodegradation of the cross‐linked collagen . Moreover, ACS can help to prevent diffusion of embedded cells when transplanted into bone defects .…”
Section: Discussionsupporting
confidence: 85%
“…An absorbable ACS (5 mm in diameter and 3 mm thick, MIGHTY; KOKEN, Tokyo, Japan) was used as a scaffold. Atelocollagen, which originates from type I collagen extracted from bovine dermis, was freeze‐dried, then cross‐linked and sterilized to produce the ACS . The ACS contains interconnected 30–200 μm pores …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was observed by Sreekumar et al that rhBMP9 treatment in human osteoblasts from 110 donors showed several advantages including higher alkaline phosphatase (ALP) activity and Smad nuclear translocation when compared to rhBMP2 and rhBMP7 by following distinct and unique signaling cascades . Thus far, two rodent studies have also demonstrated the effectiveness of rhBMP9 treatment on new bone formation when compared to untreated control sites in rat calvarial defects . However, bone inductive potential of rhBMP9 had not been investigated when compared to rhBMP2 in the animal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Further research utilizing rhBMP9 would benefit our understanding on the differential mechanisms that regulate osteogenesis in both BMP2 versus BMP9. One group currently reported that rhBMP9 loaded on atelocollagen and chitosan sponges promoted new bone formation in rat critical‐sized bone defect (Toshiaki Nakamura et al, 2016; Shinohara, Nakamura, Shirakata, & Noguchi, 2016). The further animal studies in comparison with rhBMP2 are now necessary to further verify bone regenerative potential of rhBMP9.…”
Section: Discussionmentioning
confidence: 99%